Persepsi dan Pemahaman Generasi Muda Batak Toba terhadap Hukum Perceraian Adat - Philip Marchello Hasonangan Sinaga; Sri Hadiningrum; Ananda Viranda; Jessi Aprilia Silaban; Robintang Lumban Batu (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes factors that influence this understanding and perception, such as education level, family environment, media influence, personal experience, and involvement in daily customary life. Data collection techniques are carried out through observation, interviews, and documentation in order to gain a deeper understanding of the young generation of Toba Batak towards customary divorce law. The purpose of this study is to determine the extent of the understanding of the young generation towards the customary divorce process, the role of the family, and the factors that influence their views. This study discusses the perception and understanding of the young generation of Toba Batak towards customary divorce law amidst the influence of modernization. Through the understanding and perception of the young generation towards customary divorce law, this study attempts to provide an overview of the relevance of the young generation of Toba Batak towards customary divorce law. The results of the study show that although most still respect customs and the value of family deliberation, there are doubts about customary justice, especially regarding the position of women. The young generation tends to support the preservation of customs, but hopes for adjustments to be fairer and in accordance with the times. The results of the study are expected to be input for traditional leaders and the government in designing targeted cultural preservation policies.